Experimental and Modeling Study of the Phase Behavior of (Heptane plus Carbon Dioxide plus Water) Mixtures - Al,Ghafri SZS; Forte,E; Galindo,A; Maitland,GC; Trusler,JPM (Journal of Chemical and Engineering Data, 2015)
We report experimental measurements ofthree-phase equilibria in the system (heptane + carbon dioxide+ water) obtained with a quasi-static analytical apparatus withcompositional analysis by means of gas chromatography. Theapparatus was calibrated by an absolute area method and thewhole measurement system was validated by means ofcomparison with the published literature data of the system(heptane + carbon dioxide). The compositions of the threephases coexisting in equilibrium were measured along fiveisotherms at temperatures from (323.15 to 413.15) K withpressures ranging from approximately 2 MPa to the uppercritical end point pressure at which the two nonaqueousphases became critical. The experimental results have been compared with the predictions of the statistical associating fluidtheory for potentials of variable range. The unlike binary interaction parameters used here are consistent with a previous study fora ternary mixture of a different n-alkane, while the alkane−water binary interaction parameter is found to be transferable and thealkane−carbon dioxide binary interaction parameter is predicted using a modified Hudson-McCoubrey combining rule.Generally, good agreement between experiment and theory was found